Representasi Budaya Dayak Ngaju Kaharingan dalam Ritual Tawur di Kalimantan Tengah - Valiana Sashita; Arimi, Sailal (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This article aims to investigate the sequence of events of Tawur speech in the Bayar Hajat ceremony, the meaning and function contained in Tawur speech as a form of culture of the Dayak Kaharingan community in Central Kalimantan. The source of data in this article is derived from the text of the Tawur incantation. This research method utilised ethnography and literature study. The results of the data analysis reveal that the Dayak Kaharingan community’s belief in the existence of Ranying Hattala Langit (God), Sangiang, rice spirits id reflected in the Tawur speech. In addition, the analysis also revealed a number of meanings implied in the Tawur which include, the meaning of God as the Creator, the meaning of supplication, the meaning of the existence of rice spirits and Sangiang, the meaning of respect, and the meaning of togetherness. Finally, the Tawur speech also includes two language functions, consisting of emotive function and conative function. When connected between the meaning and function contained in the Tawur speech, it is a form of creating balance, harmony, and world safety for human beings.